Semeando a restauração ecológica: semeadura direta de espécies florestais na transição Pampa – Mata Atlântica - Gazzola, Matheus Degrandi (2021)
Direct seeding of forest species has generated new possibilities for ecological restoration in the Cerrado, Atlantic Forest and Amazon biomes in Brazil. In the ecotonal transition between the Pampa and the Atlantic Forest, there are no studies that elucidate any factor that influences the performance of Direct Seeding (SD) of forest species as a technique for ecological restoration; even rarer for the region are studies that use green manure plants as facilitators in these projects. The present study evaluated the emergence and initial development of native forest species sown directly in the field, testing the coverage between the rows by green manure species as a facilitator of the initial development of seedlings. The experiment was conducted in a region of low to medium potential for natural regeneration, characterized by the transition between the Pampa and Atlantic Forest biomes, in the Central Depression of Rio Grande do Sul. Sixteen naturally occurring forest species in the region were tested in rows of direct seeding with two treatments between rows - fallow (control) and green cover with jack bean (Cannavalia ensiformis). The number of emergences, the height of seedlings and the number of leaves were evaluated monthly, for one year. Six species had established from 2 to 16% of the seeds, with a trend of success for the species with larger seeds and with emphasis on the Fabaceae family; only one species of recalcitrant seed showed emergence. The jack bean coverage provided statistically superior performance and height for Annona sylvatica and Enterolobium contortisiliquum, under the Wilcoxon test for comparison of means. The average mortality of seedlings under the green cover was half of the mortality observed in the fallow. The protection against dryness provided by the jack bean in the summer was more effective than the protection against frost in the winter, due to the sensitivity of the cover itself to the cold. Frost was found to be a limiting factor to the establishment and retarding the development of some forest species less resistant to cold, which should be taken into account in the selection of species for ecological restoration by direct seeding in the region. For the use of green manure to facilitate the initial development of forest species by direct seeding in temperate climate, it is recommended a higher density of fertilizer seeds and intercropping with other cover species, especially with moderate resistance to cold. For further research, it is recommended to go deeper into factors such as the quality and size of forest seeds, the response at different times of the year, density and sowing depth.